2019
DOI: 10.1371/journal.pone.0210468
|View full text |Cite
|
Sign up to set email alerts
|

Peer-facilitated community-based interventions for adolescent health in low- and middle-income countries: A systematic review

Abstract: BackgroundAdolescents aged 10–19 represent one sixth of the world’s population and have a high burden of morbidity, particularly in low-resource settings. We know little about the potential of community-based peer facilitators to improve adolescent health in such contexts.MethodsWe did a systematic review of peer-facilitated community-based interventions for adolescent health in low- and middle-income countries (LMICs). We searched databases for randomised controlled trials of interventions featuring peer educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
0
33
0
1
Order By: Relevance
“…We then performed a quality assessment of each study included using an 8-point scale which was first used in a meta-analysis in 200 9 [8] and has subsequently been cited by other researchers [24][25][26][27]. One point was awarded for each of the following items: (1) prospective cohort; (2) control or comparison group; (3) pre/post intervention data; (4) random assignment of participants to the intervention; (5) follow-up rate of 80% or more; (6) comparison groups equivalent in terms of social-demographic measures; (7) comparison groups equivalent at baseline in terms of outcome measures; and (8) sample size≥100.…”
Section: Data Extractionmentioning
confidence: 99%
“…We then performed a quality assessment of each study included using an 8-point scale which was first used in a meta-analysis in 200 9 [8] and has subsequently been cited by other researchers [24][25][26][27]. One point was awarded for each of the following items: (1) prospective cohort; (2) control or comparison group; (3) pre/post intervention data; (4) random assignment of participants to the intervention; (5) follow-up rate of 80% or more; (6) comparison groups equivalent in terms of social-demographic measures; (7) comparison groups equivalent at baseline in terms of outcome measures; and (8) sample size≥100.…”
Section: Data Extractionmentioning
confidence: 99%
“…29 In the current study, the peer-education strategy may have provided inadequate SRH information (intensity and duration), resulting in limited or temporary effects in promoting SRH behavior and improving adolescents' sexual health. 61 In line with this, researchers have reported that a peer-education intervention was ineffective in facilitating young people's behavioral change or influencing social norms concerning adolescent SRH. 62 In this study, a significant difference was observed between program and nonprogram areas for attitudes of adolescents toward SRH issues.…”
Section: Discussionmentioning
confidence: 95%
“…Our global systematic review found that peerfacilitated interventions could be beneficial across a range of areas of health, with the strongest evidence for mental health [20]. Our review of Indian national and local adolescent health programmes found that many existed but had been designed and implemented by multiple governmental and non-governmental agencies, resulting in a lack of coordination and overlap.…”
Section: Formative Research To Develop a Community Adolescent Health mentioning
confidence: 96%
“…We will use the Food and Nutrition Technical Assistance tool to measure mean dietary diversity score (based on 24-h recall) [19]. For mental health problems, we will compare the mean score on the Brief Problem Monitor-Youth (BPM-Y) across trial arms [20]. The BPM-Y includes items on internalising (depression and anxiety), externalising (conduct disorder and oppositional defiant disorder) and attention problems.…”
Section: Study Outcomesmentioning
confidence: 99%